Efecto de klip algodón y klip calcio boro sobre la producción de algodón: informe final, proyecto no. 77-02. - Salazar, Faunier; Mosquera París, L.F.; Cuéllar, R. (Compañía Colombiana de Inversiones Agrícolas, 2018)
Algodón-Gossypium herbaceum